Psychological and traumatic stress and the risk of developing diabetes and psychiatric disorders after a disaster-relief mission: An eight-year longitudinal study of Japan Maritime Self-Defense Force personnel dispatched for the 2011 Great East Japan Earthquake disaster-relief mission. (February 2022) - Tanaka, Teppei; Takeshita, Shogo; Inoue, Takeshi; Yoshino, Aihide; Sawamura, Takehito; Toda, Hiroyuki
Abstract: The Great East Japan Earthquake caused triple disasters—the earthquake itself, tsunamis, and nuclear leakage. Japan Maritime Self-Defense Force (JMSDF) personnel engaged in disaster-relief suffered various degrees of psychological stress, which is associated with psychiatric as well as physical disorders, such as diabetes. This study aimed to assess the effect of mission-related stress on the development of diabetes and psychiatric disorders in these personnel using JMSDF annual physical check-up data from 2010 to 2018 and Impact of Events Scale-Revised (IES-R) and Kessler Psychological Distress Scale (K-10) questionnaire data. Cox proportional hazard models were used to assess the hazard ratios (HRs) of developing diabetes and psychiatric disorders in the dispatched (N = 3686) vs. non-dispatched (N = 13, 953) groups and high IES-R (score ≥25) vs. low IES-R score and high K-10 (score ≥25) vs. low K-10 score subgroups. We found a significantly higher HR of developing diabetes in the high IES-R score subgroup (2.02; 95% confidence interval [CI], 1.08–3.80). However, the HRs were not significant when comparing dispatched vs. non-dispatched groups and high vs. low K-10 score subgroups. Although the HR of developing psychiatric disorders was significantly lower in the dispatched group (0.64; 95% CI, 0.48–0.84), it was significantly higher in the high IES-R (7.95; 95% CI, 3.38–18.74) and high K-10 (8.76; 95% CI, 4.34–17.68) score subgroups. Thus, this study indicates the importance of paying closer attention to the risk of diabetes and psychiatric disorders in individuals with high IES-R or K-10 scores after disaster-relief activities. Highlights: Risk of diabetes and psychiatric disorders was studied in disaster-relief workers. High post-traumatic stress responses were the risk for diabetes. High post-traumatic stress responses were the risk for psychiatric disorders. High general psychological distress was also the risk for psychiatric disorders.